Antibody attributes, Fc receptor expression, gestation and maternal SARS-CoV-2 infection modulate HSV IgG placental transfer - Aakash Mahant Mahant; Fatima Estrada Trejo; Jennifer T. Aguilan; Simone Sidoli; Sallie R. Permar; Betsy C. Herold (iScience, 2023)
Summary: Antibody-dependent cellular cytotoxicity (ADCC) is associated with protection against neonatal herpes. We hypothesized that placental transfer of ADCC-mediating herpes simplex virus (HSV) immunoglobulin G (IgG) is influenced by antigenic target, function, glycans, gestational age, and maternal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Maternal and cord blood were collected from HSV-seropositive (HSV+) mothers pre-COVID and HSV+/SARS-CoV-2+ mothers during the pandemic. Transfer of HSV neutralizing IgG was significantly lower in preterm versus term dyads (transfer ratio [TR] 0.84 vs. 2.44) whereas the TR of ADCC-mediating IgG was <1.0 in both term and preterm pre-COVID dyads. Anti-glycoprotein D IgG, which had only neutralizing activity, and anti-glycoprotein B (gB) IgG, which displayed neutralizing and ADCC activity, exhibited different relative affinities for the neonatal Fc receptor (FcRn) and expressed different glycans. The transfer of ADCC-mediating IgG increased significantly in term SARS-CoV-2+ dyads. This was associated with greater placental colocalization of FcRn with FcγRIIIa. These findings have implications for strategies to prevent neonatal herpes.